MODELS OF RESEARCH TEAMS IN THE MANAGEMENT OF A MODERN RUSSIAN SOCIETY: TRADITION AND INNOVATION - Andrey Lezhebokov; Elena Sergodeeva (Вестник Северо-Кавказского федерального университета)
The article describes the traditional for Russian higher education model research teams management, substantiated the main problems for its effective use in the contemporary socio-economic and cultural conditions, we analyzed the conceptual approaches to the construction of a modern system of management of higher education institutions through the process of formation and set out basic principles for successful implementation and implementation of innovative models of scientific and educational organizations management.